اگر $\overset{\to }{\mathop{b}}\,=\left[ \begin{matrix} -4 \\ 2 \\ \end{matrix} \right],\overset{\to }{\mathop{a}}\,=\left[ \begin{matrix} 3 \\ -2 \\ \end{matrix} \right]$ آنگاه $\overset{\to }{\mathop{c}}\,=\overset{\to }{\mathop{a}}\,-2\overset{\to }{\mathop{b}}\,$ برابر است با :
1 )
$\left[ \begin{matrix} -14 \\ 6 \\ \end{matrix} \right]$
2 )
$\left[ \begin{matrix} 11 \\ 6 \\ \end{matrix} \right]$
$\left[ \begin{matrix} 11 \\ -6 \\ \end{matrix} \right]$
4 )
$\left[ \begin{matrix} 14 \\ -6 \\ \end{matrix} \right]$